2021
DOI: 10.1111/liv.15080
|View full text |Cite
|
Sign up to set email alerts
|

The burden and sexual dimorphism with nonalcoholic fatty liver disease in Asian children: A systematic review and meta‐analysis

Abstract: Background: Despite substantial attention paid to the epidemic of nonalcoholic fatty liver disease (NAFLD) in adults, data on the burden and sexual dimorphism of NAFLD in Asian children have not yet been synthesized. Methods:We conducted a literature search of 735 references up to April 2021.Pooled analyses, stratified analyses and meta-regression were all performed.Results: Thirty-three study populations were finally included. Nine of them comprising 20 595 children showed an overall NAFLD prevalence of 5.53%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 44 publications
2
15
0
Order By: Relevance
“…[ 27 ] In Asia, the prevalence of pediatric MAFLD has been increasing, particularly in obese male population over the age of 10. [ 28 ] In the US, as reported in the “Study of Child and Adolescent Liver Epidemiology (SCALE)”, MAFLD is present in 5% to 10% of children/adolescents aged 2 to 19 years. [ 26 ] A meta-analysis by Anderson et al [ 27 ] found that MAFLD prevalence in the general pediatric population ranged from 9% to 37%.…”
Section: Mafld In Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 27 ] In Asia, the prevalence of pediatric MAFLD has been increasing, particularly in obese male population over the age of 10. [ 28 ] In the US, as reported in the “Study of Child and Adolescent Liver Epidemiology (SCALE)”, MAFLD is present in 5% to 10% of children/adolescents aged 2 to 19 years. [ 26 ] A meta-analysis by Anderson et al [ 27 ] found that MAFLD prevalence in the general pediatric population ranged from 9% to 37%.…”
Section: Mafld In Childrenmentioning
confidence: 99%
“…Interestingly, the prevalence of MAFLD in pediatric populations differs between regions with the highest prevalence in Asia [27] . In Asia, the prevalence of pediatric MAFLD has been increasing, particularly in obese male population over the age of 10 [28] . In the US, as reported in the “Study of Child and Adolescent Liver Epidemiology (SCALE)”, MAFLD is present in 5% to 10% of children/adolescents aged 2 to 19 years [26] .…”
Section: Mafld In Childrenmentioning
confidence: 99%
“…Regarding pediatric NAFLD, Zou et al implemented a systematic review and found that more than one‐third of children with NAFLD had elevated levels of ALT, indicating high proportion of possible nonalcoholic steatohepatitis (NASH) in children 6 . Boys were more prone to have NAFLD than girls after 10 years old.…”
Section: Non‐alcoholic Fatty Liver Diseasementioning
confidence: 99%
“…The pooled prevalence of NAFLD in Asian children increased from those with normal weight (1.5%) to those who were overweight (16.7%) or obese (50.1%). [ 2 ]…”
mentioning
confidence: 99%
“…The pooled prevalence of NAFLD in Asian children increased from those with normal weight (1.5%) to those who were overweight (16.7%) or obese (50.1%). [2] A recent study suggested that NAFLD is not uncommon in lean Chinese adults with a normal waist circumstance. Metabolic risk factors, rather than genetic factors, may play an important role in the development of lean NAFLD, [3] and the hepatic and extra-hepatic complications can also develop in lean patients, which reinforces the importance of considering metabolic phenotype in the assessment of NAFLD, rather than using body mass index-based approaches.…”
mentioning
confidence: 99%